PENGARUH USIA KEHAMILAN TERHADAP GANGGUAN TIDUR PADA IBU HAMIL DI PBM ERNA PENIWATI DESA BALONG KECAMATAN BALONG PONOROGO - Ambika Kurnia Mustikawati (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2018)
Pregnancy is a valuable thing, but also one of the great stresses for a woman both physically and mentally. Physical comfort disorders at each stage of gestational age vary due to interrupt the rest of pregnant women. This sleep disorder causes hypertension, exhaustion and disrupt activity. Interview results, 7 out of 10 pregnant women said experiencing sleep disorders. The purpose of this study was to analyze the effect of gestational age on sleep disturbance.The research type is analytic with cross-sectional approach. Research location in PMB Erna Peniwati Desa Balong Kabupaten Ponorogo. The study was conducted on May 15 to June 10, 2018. Determination of the sample using a simple random sampling technique of 40. Dependent variable is sleep disturbance, while the independent variable is the age of pregnancy. Data collection techniques using questionnaires. Data analysis using Pearson test with the help of computer program SPSS 22,0 for windows.The results showed that from 40 respondents, half of which were 20 (50%) of pregnant women TM 3 had moderate sleep disorder and almost half that is as many as 12 (30%) pregnant women TM 2 had mild sleep disorder. Result of calculation using Pearson statistic test with significant level 0,01 that is p = 0,000 <α 0,01 meaning Ho rejected and H1 accepted, so there is influence between pregnancy age with sleep disorder in pregnant woman in PMB Erna Peniwati with correlation coefficient 0,572 indicating closeness strong influence.Different pregnancy rates affect sleep disturbance in each pregnant woman especially in the 3rd trimester pregnant women. It is expected to place the research to provide a solution for pregnant women so as to reduce the perceived sleep disturbance and respondents are expected to have a good way of dealing with sleep disorders for their health and the fetus and preparation for labor.